Suicidality in Fibromyalgia: A Systematic Review of the Literature - Levine, Daniella; Horesh, Danny (Frontiers in Psychiatry, 2020)
Fibromyalgia (FM), a poorly understood rheumatic condition, is characterized by chronic pain and psychiatric comorbidities, most notably depression and anxiety. Additional symptoms include sleep difficulties, fatigue, and various cognitive impairments. Furthermore, FM is surrounded by social stigma, due to the unclear nature and etiology of this condition. While there is widespread evidence for the emotional and psychological suffering of those with FM, the scope of suicidality, as well as the underlying factors that are associated with suicidal ideation and behavior among this population, are not well understood. The present review, which is the first of its kind, aims to summarize existing data on the prevalence of suicide-related outcomes among FM patients, highlight factors associated with suicidal ideation and behavior in FM, and identify gaps in the literature to better inform research and clinical care. Studies were extracted from the literature that measured suicidal ideation, attempted suicide, and/or completed suicide among FM patients. Results indicated that both suicidal ideation and suicidal behavior were prevalent among individuals suffering from FM. Psychiatric comorbidity, sleep difficulties, and inpatient hospitalization were associated with both suicidal ideation and suicidal behavior. Functional impairment was associated with suicidal ideation in FM. Factors associated with higher levels of suicidal behavior in FM included female gender, unemployment and lower income, medical comorbidity, and drug dependence. While an understanding of currently recognized risk factors is important for improving FM research and clinical care, some clear methodological and conceptual limitations of the reviewed studies were identified. Future work should focus on longitudinal studies, as well as on gaining a better biological and psychological understanding of the underpinnings of FM and suicidality.